Don't blink now! : capturing the hidden world of sea creatures - Downer, Ann, 1960- (New York : F. Watts, 1991)
Underwater photographs capture marine animals in the acts of birth, growth, the hunt, and death.
"A New England Aquarium book.".
Includes bibliographical references (p. 37-39) and index.
Appraisal-Science Books for Young People.
School Library Journal.
6.7
5-8
Keywords: Marine fauna -- Juvenile literature; Marine animals; Marine animals